Kapasitas Daya Tampung Hijauan Pakan Ternak dan Hasil Ikutan Perkebunan Kelapa Sawit di Kecamatan Tanggetada Kabupaten Kolaka - Muhammad Amrullah Pagala; Deki Zulkarnain; La Ode Muhammad Munadi (Universitas Halu Oleo, 2020)
The purpose of this study was to determine the carrying capacity of forage and the by-product of oil palm plantations as feed for Bali cattle in Tanggetada District. This research method was carried out by observing the forage potential of feed ingredients based on the production of feed ingredients multiplied by the harvested area and expressed in dry matter (BK). Sampling was carried out by sampling / tiling for animal feed. Forage as research material is grasses, leguminous pods and by-products of oil palm plantations. The method of data analysis uses regional capacity analysis. The results showed that there were 9 types of forage, 2 types of leguminous pods, 2 types of puzzle puzzles and 4 types of plantation waste as animal feed identified in Tanggetada District The production of forage dry materials and by-products of palm oil could meet the consumption needs of Bali cattle in Tanggetada District. The results of the capacity analysis show that Tanggetada District has the ability of the area to accommodate 28,292 Bali cattle from a total population of Bali cattle of 2,338.Keywords: carrying capacity forage; results of oil palm plantation; Tanggetada